An Atopic Dermatitis-Like Mouse Model by Alternate Epicutaneous Application of Dinitrofluorobenzene and an Extract of Dermatophagoides Farinae - Feng, Shujing; Liu, Wengying; Deng, Sisi; Song, Guoxuan; Zhou, Jie; Zheng, Zhengni; Song, Zhiqiang (Frontiers in Medicine, 2022)
Several studies have tried to establish mice models of atopic dermatitis (AD) through the allergen of Dermatophagoides farinae (Df). However, there are no skin lesions after epicutaneous application of an extract of Df (DfE) on BALB/c mice. Dinitrofluorobenzene (DNFB) is a common hapten to bring about contact dermatitis. The skin dysfunction induced by DNFB may be a way to enhance the effects of DfE on mice skin. Thus, we hypothesized that alternate epicutaneous application of DNFB and DfE could induce AD-like skin lesions on BALB/c mice. To test this hypothesis, we alternately applied the DNFB and DfE to the back skin of BALB/c mice for 8 weeks. Changes of mice skin lesions and the frequency of scratching behavior got record. The variation of Th1-related cytokines (IFN-γ, IL-2) and Th2-related cytokines (IL-4, IL-13) was detected in serum and lesional skin. Eventually the BALB/c mice developed severe erythema, erosion, scarring and excoriation on the entire back, showing a high frequency of scratching behavior. In addition, Th2 cells dominant cytokines appeared in both serum and lesional skin. Those results indicate that alternating epicutaneous exposure to DNFB and DfE can produce AD-like models with typical clinical features and Th2-type immune responses in BALB/c mice. This model would be valuable for studying the pathogenesis of AD and developing novel therapeutic agents for it.